A school of its own: US naturalism and the demands of professional labor - Löffler, Philipp (College literature, 2024)
This essay centers around a comparative reading of William Dean Howells's A Hazard of New Fortunes and Frank Norris's McTeague. Its main goal is to contextualize Norris's attempts to promote what he understood to be literary naturalism—positioned against the "well-behaved, ordinary, bourgeois" realism of Howells—and to show how he connected the idea of 'the literary' to the postbellum world of professional labor. In as much as other, established professions already regulated the practice of work according to internally ratified standards of quality, postbellum writers, too, sought to render the practice of writing objectifiable by appeal to standards of evaluation that were approved by experts within their own community, a "brotherhood of novelists" in the words of James.